2021
DOI: 10.1186/s13148-021-01019-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation impact on Fabry disease

Abstract: Background Fabry disease (FD) is a rare X-linked disease caused by mutations in GLA gene with consequent lysosomal accumulation of globotriaosylceramide (Gb3). Women with FD often show highly heterogeneous symptoms that can manifest from mild to severe phenotype. Main body The phenotypic variability of the clinical manifestations in heterozygous women with FD mainly depends on the degree and direction of inactivation of the X chromosome. Classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
(113 reference statements)
1
12
0
Order By: Relevance
“…Although few studies have dealt with the role of methylation in FD, for a review see Di Risi et al ( 24 ); the present study provided further evidence on the potential role of DNA methylation involvement in the clinical manifestation of FD. The GLA mutations can cause total or partial decreased activity of α-Gal A and accumulation of glycosphingolipids ( 3 , 4 ).…”
Section: Discussionsupporting
confidence: 64%
“…Although few studies have dealt with the role of methylation in FD, for a review see Di Risi et al ( 24 ); the present study provided further evidence on the potential role of DNA methylation involvement in the clinical manifestation of FD. The GLA mutations can cause total or partial decreased activity of α-Gal A and accumulation of glycosphingolipids ( 3 , 4 ).…”
Section: Discussionsupporting
confidence: 64%
“…Hossain et al [ 14 , 15 ] directly analyzed methylation of the GLA gene in female Fabry patients, and showed that methylation of the non-mutated allele correlated with disease severity. These studies highlighted the potential effect of methylation of GLA gene on α-gal A activity and disease phenotype in heterozygous females (for a review on the role of DNA methylation in Fabry disease, see Di Risi et al [ 16 ]). However, the role of epigenetic modifications as a downstream mediator in disease pathogenesis has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the DNA methylation of promoter CpG island (PCGI) associated with GBM disease progression, we established a richly computational strategy that maps the Infinium HumanMethylation450K microarray to gene PCGI methylation profiles and summarizes DNA methylation patterns at the gene level ( Zhao et al, 2021b ). First, based on the gene annotation derived from the GENCODE database and GPL13534 platform file containing the methylation probes information ( Li et al, 2020 ; Di Risi et al, 2021 ), we defined the promoter region as 2 kb located upstream of the transcription start site ( Hollstein et al, 2019 ). We extracted the relevant probes on the PCGI from the annotation file for subsequent analysis ( Carro et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we downloaded gene expression data from the Chinese Glioma Genome Atlas (CGGA, http://www.cgga.org.cn/ ) database as a supplementary dataset, which includes 282 GBM patients who possessed complete clinical information ( Zhao et al, 2021a ). The annotation file for mRNAs and promoter region was derived from the GENCODE database ( https://www.gencodegenes.org/ ) ( Di Risi et al, 2021 ). The single-cell sequencing data were obtained from GSE162631 in the GEO database, and cells derived from the tumor cores of three GBM patients in the dataset were selected ( Xie et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%